2015
DOI: 10.1007/978-3-319-15994-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Towards Linked Data Conventions for Delivery of Environmental Data Using netCDF

Abstract: Part 2: Information Systems, Information Modelling and SemanticsInternational audiencenetCDF is a well-known and widely used format to exchange array-oriented scientific data such as grids and time-series. We describe a new convention for encoding netCDF based on Linked Data principles called netCDF-LD. netCDF-LD allows metadata elements, given as string values in current netCDF files, to be given as Linked Data objects. netCDF-LD allows precise semantics to be used for elements and expands the type options be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…While Yu et al [5] proposed and Baird et al [6] have demonstrated sophisticated integration of Linked Data into netCDF files, we have tested simples of integrations only whereby we place Universal Resource Indicator (URI) links [8] to SKOS concepts within attribute metadata in netCDF files. Our reason for taking this very simple approach is to enable the demonstration, and ultimately the adoption, of some limited Linked Data and Semantic Web functionality with the lowest possible barrier to uptake.…”
Section: Simple Linked Data Encodingmentioning
confidence: 99%
See 4 more Smart Citations
“…While Yu et al [5] proposed and Baird et al [6] have demonstrated sophisticated integration of Linked Data into netCDF files, we have tested simples of integrations only whereby we place Universal Resource Indicator (URI) links [8] to SKOS concepts within attribute metadata in netCDF files. Our reason for taking this very simple approach is to enable the demonstration, and ultimately the adoption, of some limited Linked Data and Semantic Web functionality with the lowest possible barrier to uptake.…”
Section: Simple Linked Data Encodingmentioning
confidence: 99%
“…The netCDF specification includes a set of software tools used to manipulate netCDF files [6]. These tools allow people to view netCDF metadata and data, create netCDF files and view visual representations of netCDF's gridded arrays.…”
Section: The Ncskosdump Toolmentioning
confidence: 99%
See 3 more Smart Citations